2020
DOI: 10.1136/heartjnl-2019-316007
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of von Willebrand factor in adult patients with congenital heart disease

Abstract: Objectivesvon Willebrand factor (vWF) has prognostic value in patients with heart failure (HF) and in those with liver disease. Liver congestion, due to right-sided HF (RHF), is one of the major clinical pathophysiologic manifestations in adults with congenital heart disease (ACHD). The present study’s purpose was to clarify the prognostic value of plasma levels of vWF antigen (vWF:Ag) in ACHD.MethodsWe measured vWF:Ag (%) in 382 consecutive patients (20 unrepaired cyanotic ACHD, 172 Fontan patients and 190 AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…A retrospective cohort study showed MELD-XI remained a significant predictor of MACE in ACHD patients after adjusting for patient characteristics, including sex, functional status, estimated glomerular filtration rate, and cardiac function, while predictive modeling revealed it to be most important variable predicting MACE in this population [70]. Biomarkers may also assist in risk stratification of patients with ACHD and liver complications, with prime candidates including galectin-3 and von Willebrand factor antigen [71,72].…”
Section: Hepatic Dysfunctionmentioning
confidence: 99%
“…A retrospective cohort study showed MELD-XI remained a significant predictor of MACE in ACHD patients after adjusting for patient characteristics, including sex, functional status, estimated glomerular filtration rate, and cardiac function, while predictive modeling revealed it to be most important variable predicting MACE in this population [70]. Biomarkers may also assist in risk stratification of patients with ACHD and liver complications, with prime candidates including galectin-3 and von Willebrand factor antigen [71,72].…”
Section: Hepatic Dysfunctionmentioning
confidence: 99%
“…Plasma von Willebrand factor (vWF) is certainly a nice candidate for a prognostic marker(figure 1) As Ohuchi et al 6 outline, in this issue of Heart , vWF is easily and inexpensively obtainable as a plasma sample and is known to be elevated with endothelial dysfunction or hepatic fibrosis. This latter is an important consideration in some CHD pathologies, where significant right ventricular dysfunction is a key feature and contributes to morbidity and mortality.…”
mentioning
confidence: 99%